Rewriting the Textbook: an investigation into students’ practices with creative composition in a Year 7 Latin class - Adam Trusted (The Journal of Classics Teaching)
This project investigated the effectiveness of a creative Latin composition exercise. Within this exercise, students built upon existing Latin textbook material, inserting their own character into an existing Cambridge Latin Course (CLC) story (CSCP, 1998). This form of exercise has links to more conventional prose composition exercises, but it also takes inspiration from exercises which use fanfiction to improve language skills (Bahoric and Swaggerty, 2015).